Estimating the physicochemical properties of polyhalogenated aromatic and aliphatic compounds using UPPER: Part 1. Boiling point and melting point. (January 2015) - Admire, Brittany; Lian, Bo; Yalkowsky, Samuel H.
Highlights: UPPER uses enthalpic and entropic descriptors to predict physicochemical properties. 19 new group descriptors are added to predict the transition temperatures compounds. Boiling point of 808 compounds predicted with an average absolute error of 13.56 K. Melting point of 742 compounds predicted with an average absolute error of 25.85 K. Abstract: The UPPER (Unified Physicochemical Property Estimation Relationships) model uses enthalpic and entropic parameters to estimate 20 biologically relevant properties of organic compounds. The model has been validated by Lian and Yalkowsky on a data set of 700 hydrocarbons. The aim of this work is to expand the UPPER model to estimate the boiling and melting points of polyhalogenated compounds. In this work, 19 new group descriptors are defined and used to predict the transition temperatures of an additional 1288 compounds. The boiling points of 808 and the melting points of 742 polyhalogenated compounds are predicted with average absolute errors of 13.56 K and 25.85 K, respectively.